Pengaruh Pendapatan Asli Daerah (PAD) Dana Alokasi Umum (DAU) Dana Alokasi Khusus (DAK) Terhadap Belanja Daerah (Studi Kasus Pada Kabupaten di Provinsi Jawa Tengah) - Leni Sofiyani; Subadriyah Subadriyah (Jurnal Rekognisi Akuntansi, 2020)
This study aims to find out and analyze whether Regional Original Income, General Allocation Fund, Special Allocation Fund, affects District / City Spending in Central Java Province. The analysis method used is a quantitative method, with multiple regression testing by conducting a classical assumption test before getting the best research model. The variables in this study are Regional Original Income, General Allocation Fund, Special Allocation Fund as independent variables, while dependent variables are Regional Spending. The population is the entire city regency in Central Java Province as many as 35 regencies / cities. The data used in this study is data taken from 2016 to 2018. The data analyzed in this study is secondary data sourced from the District / City APBD Realization Report in Central Java Province obtained from the Local Government Financial Balance site on the internet (www.djpk.depkeu.go.id). From the data, then conducted a research analysis using multiple linear regression techniques with SPSS 23. The results of this study prove that The Regional Original Income has a positive impact on Regional Spending, the General Allocation Fund has no effect on Regional Spending, The Khusu Allocation Fund has a positive effect on Regional Spending.